2012
DOI: 10.1088/0004-637x/756/2/192
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fast Magnetosonic Waves in the Release and Conversion via Reconnection of Energy Stored by a Current Sheet

Abstract: Using a simple two-dimensional, zero-β model, we explore the manner by which reconnection at a current sheet releases and dissipates free magnetic energy. We find that only a small fraction (3%-11% depending on currentsheet size) of the energy is stored close enough to the current sheet to be dissipated abruptly by the reconnection process. The remaining energy, stored in the larger-scale field, is converted to kinetic energy in a fast magnetosonic disturbance propagating away from the reconnection site, carry… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 24 publications
(71 reference statements)
2
29
0
Order By: Relevance
“…This elimination is meant to represent those processes which stop the tube, including the emission of fast magnetosonic waves or even formation of a fast magnetosonic termination shock. Longcope & Tarr (2012) argued, using a crude two-dimensional MHD calculation, that the process of eliminating a CS by reconnection could produce fast magnetosonic waves carrying roughly this fraction of the released energy.…”
Section: Discussionmentioning
confidence: 99%
“…This elimination is meant to represent those processes which stop the tube, including the emission of fast magnetosonic waves or even formation of a fast magnetosonic termination shock. Longcope & Tarr (2012) argued, using a crude two-dimensional MHD calculation, that the process of eliminating a CS by reconnection could produce fast magnetosonic waves carrying roughly this fraction of the released energy.…”
Section: Discussionmentioning
confidence: 99%
“…Everywhere else the current is very low. In contrast to Longcope and Priest [] and Longcope and Tarr [], (zero‐beta models), the numerical models of Fuentes‐Fernández et al [] (high beta) and Fuentes‐Fernández et al [] (low beta) find that the reconnection process converted most of the magnetic energy (stored in the 2‐D null current layer configuration) directly into internal energy, via Ohmic dissipation, with only a little being converted initially into kinetic energy and then damped due to viscosity. Additionally, Fuentes‐Fernández et al [] found that the value of the magnetic diffusivity affects not only the reconnection rate but also the amount of magnetic energy converted into kinetic and internal energy.…”
Section: Introductionmentioning
confidence: 98%
“…Waves and Poynting flux are also receiving renewed attention in reconnection theory, where studies by Longcope & Priest (2007), Birn et al (2009), Kigure et al (2010), and Longcope & Tarr (2012) have highlighted their role carrying signals and energy away from the reconnection site into the surrounding medium. These aspects are particularly apparent if reconnection is time-dependent, conditions are low-beta, waves are allowed to freely propagate away from the reconnection site without being reflected by artificial boundaries, and resistivity is small or localised to the reconnection site so that waves are not artificially overdamped.…”
Section: Introductionmentioning
confidence: 99%